Electoral secularism in Singapore : political responses to homosexuality - Walid Jumblatt Abdullah (2021)
In recent years, the interventionist self-avowed secular state of Singapore, like many non-Western countries, has had to wrestle with the issue of homosexuality and Lesbian, Gay, Transsexual and Bisexual (LGBT) rights. Managing the demands of the conservative elements of society alongside the increasingly vocal liberal factions is a priority for a state whose legitimacy depends, in large part, on maintaining social order. This article makes the following argument. Contrary to what has been suggested by some commentators, the Singaporean state does not have an ideological preference in this matter. As such, it is willing to pander to both the liberal and conservative segments of society, and does so by retaining the anti-homosexuality law (known colloquially as §377A) while promising not to enforce it. This is what I term “electoral secularism”: in cases involving religion whereby the state has no firm predisposition, it attempts to adopt a position that is likely to please as many of its citizens as it can, or at least one that will antagonise as few as possible. The concept of electoral secularism is antithetical to the notion that secularism necessarily and always entails a principled stance of separation between church and state.